Helmintofauna associada a répteis provenientes da Reserva Particular do Patrimônio Natural Foz do Rio Aguapeí, estado de São Paulo - Silva, Lidiane Aparecida Firmino da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The biomes Atlantic Forest and Savannah hold contact points known as “transition areas”. Such areas are highly complex because they harbor elements belonging to the two biomes and also distinct elements, which make them relevant due to the possibility of endemism. The aim of this study was to characterize the composition and structure of the helminth fauna associated with reptiles from a biome of transition area, located in the National Park “Foz do Aguapeí” (Reserva Particular do Patrimônio Natural – RPPN - Foz do Rio Aguapeí), Northwest portion of São Paulo State, Castilho municipality. It was necropsied 88 reptile specimens, comprised by five snake families (Boidae, Colubridae, Dipsadidae, Typhlopidae and Viperidae), five lizard families (Diploglossidae, Gymnophthalmidae, Mabuyidae, Teiidae and Tropiduridae), one crocodile family (Alligatoridae), and one chelonian family (Chelidae). A total parasite prevalence of 57% was observed. The helminthes recuperated represent 27 taxa: Acanthocephala (Cystacanth), Digenea (Cheloniodiplostomum testudinis, Infidum infidum, Infidum similis, Nematophila grandis, Telorchis birabeni, Travtrema stenocotyle and two unidentified morpho-types), Monogenea (Polystomoides brasiliensis and Polystomoides sp.), Cestoda (Crepidobothrium cf. gerrardii, Oochoristica sp. and Ophiotaenia sp.) and Nematoda (Brevimulticaecum sp., Brevimulticaecum pintoi, Cistos, Cosmocerca podicipinus, Hastospiculum digiticaudatum, Ortleppascaris alata, Parapharyngodon largitor, Physaloptera sp., Physalopteroides sp., Rhabdias sp., Serpinema monospiculatus, Spiroxys figuereidoi and Strongyloides ophidae). This study records 25 new hosts for different helminth species, and represents an important contribution for the knowledge of helminth fauna associated with reptiles from South America, broadening the parasitism records of hosts from the Neotropical region

Os biomas de Mata Atlântica e Cerrado possuem pontos de contato conhecidos como “áreas de transição”, as quais são altamente complexas por abrigarem elementos dos dois biomas e ainda elementos distintos, o que as tornam de alta relevância, devido à possibilidade de endemismos. O objetivo deste estudo foi descrever a helmintofauna associada à répteis de uma região caracterizada por bioma de transição, localizado na unidade de conservação da Reserva Particular do Patrimônio Natural (RPPN) Foz do Rio Aguapeí, porção Noroeste do Estado de São Paulo, município de Castilho. Foram necropsiados 88 espécimes de répteis, representados por cinco famílias de serpentes (Boidae, Colubridae, Dipsadidae, Typhlopidae e Viperidae), cinco de lagartos (Diploglossidae, Gymnophthalmidae, Mabuyidae, Teiidae e Tropiduridae), uma de crocodilianos (Alligatoridae) e uma de quelônio (Chelidae). A prevalência parasitária total observada foi de 57%. Vinte e sete taxa de helmintos foram recuperados: Acanthocephala (Cistacanto), Digenea (Cheloniodiplostomum testudinis, Infidum infidum, Infidum similis, Nematophila grandis, Telorchis birabeni, Travtrema stenocotyle e dois morfotipos não identificados), Monogenea (Polystomoides brasiliensis e Polystomoides sp.), Cestoda (Crepidobothrium cf. gerrardii, Oochoristica sp. e Ophiotaenia sp.) e Nematoda (Brevimulticaecum sp., Brevimulticaecum pintoi, Cistos, Cosmocerca podicipinus, Hastospiculum digiticaudatum, Ortleppascaris alata, Parapharyngodon largitor, Physaloptera sp., Physalopteroides sp., Rhabdias sp., Serpinema monospiculatus, Spiroxys figuereidoi e Strongyloides ophidae). Este estudo registra 25 novos hospedeiros para diferentes espécies de helmintos. Além de representar uma importante contribuição para o conhecimento da helmintofauna associada à répteis da América do Sul, aumentando o conhecimentos do parasitismo nesses hospedeiros da região neotropical
Keywords: Helminto - Composição; Vertebrado; São Paulo (Estado); Relação hospedeiro-parasito; Helminthology